'Being in it together': living with a partner receiving deep brain stimulation for advanced Parkinson's disease – a hermeneutic phenomenological study. (15th April 2012) - Haahr, Anita; Kirkevold, Marit; Hall, Elisabeth O.C.; Østergaard, Karen
<x xml:space="preserve">Abstract</x> haahr a., kirkevold m., hall e.o.c. & østergaard k. (2012) 'Being in it together': living with a partner receiving deep brain stimulation for advanced Parkinson's disease – a hermeneutic phenomenological study. Journal of Advanced Nursing69(2), 338–347. doi: 10.1111/j.1365‐2648.2012.06012.x Abstract Aim. This article is a report of an exploration of the lived experience of being a spouse to a person living with advanced Parkinson's disease, before and during the first year of deep brain stimulation. Background. Parkinson's disease is a chronic progressive neurodegenerative disease. It has a profound impact on the everyday life for patients and spouses. Deep brain stimulation is offered with the aim of reducing symptoms of Parkinson's disease. The treatment is known to improve quality of life for patients, but little is known of how spouses experience life following their partners' treatment. Design. A longitudinal interview study with a hermeneutic phenomenological approach. Method. Ten spouses were included in the study. Data were gathered in 2007–2008, through qualitative in‐depth interviews with spouses once before and three times during the first year of their partners' treatment with Deep Brain Stimulation. Data collection and data analysis were influenced by the hermeneutic phenomenological methodology of van Manen. Findings. The uniting theme 'Solidarity – the base for joined responsibility and concern' was the foundation for the relationship between spouses and their partners. Before treatment, the theme 'Living in partnership' was dominant. After treatment two dichotomous courses were described 'A sense of freedom embracing life' and 'The challenge of changes and constraint'. Conclusion. Spouses are deeply involved in their partners' illness and their experience of life is highly affected by their partners' illness, both before and after deep brain stimulation. The relationship is founded on solidarity and responsibility, which emphasizes spouses' need to be informed and involved in the process following Deep Brain Stimulation.